Sistematización de experiencias del proyecto Paz y Región llevado a cabo en Pajonales S.A.S. entre agosto y noviembre de 2023: La importancia de un área de comunicaciones en la empresa (2024)
This systematization of experiences accounts for the work creating content for social networks that I carried out between August and November 2023 with the Pajonales S.A.S organization located in the municipality of Ambalema, Tolima. The main objective of this research is to demonstrate the importance of a consolidated and independent communications area that proposes external communication strategies within an organization like Pajonales, given that this was a determining factor when performing my duties as social communicator and journalist and obtain maximum performance. The theoretical paradigms addressed were organizational communication, communication management, cultural convergence and functionalism. This work appealed to the systematization of experiences as a methodological model based on five stages: the starting point: the experience, formulating a systematization plan, the recovery of the process experienced, the background reflections and the arrival points. The above allowed us to conclude that the presence of a communications area is essential for the correct functioning of external communication in a company and that the correct investment in this area allows Pajonales S.A.S to be competitive in the contemporary market.